EFEK EKSPLOITASI MEDIA MASSA TERHADAP POPULARITAS PRESIDEN BARRACK OBAMA DI KALANGAN AKTIVIS MAHASISWA KOTAMAKASSAR - Arifuddin, Arifuddin Arifuddin; Kartika, Nanda Sukmawati (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2010)
This study aims to determine the influence of mass media on issues significant to the popularity of Obama s U.S. presidential election and the 2009-2014 exploitation of mass media effects on the formation of opinion among student activists in Makassar. This is a descriptive qualitative research. Data obtained from interviews with the informants research namely Makassar student activist who was taken from the Universitas Hasanuddin, Universitas Muslim Indonesia, Universitas 45, State University of Makassar, Alauddin State Islamic University, Makassar. The unit of analysis is the study of mass media about Barack Obama s Indonesia during the period mid 2008 - early 2009 with news of Obama s racial identity, the background of Obama and the Muslim world, and Obama s child hoodin Indonesia. The result showed that the mass media can give the slightest effect when the audience is continuously exposed. In this research found that mass media is believed by student activists to give effect to the formation of public opinion is television, internet, and newspapers. Then the social categories that same level in this group of student activists in Makassar likely to provide a uniform response to media exposure.